Oesophagectomy with or without supraclavicular lymphadenectomy after neoadjuvant treatment for squamous cell carcinoma of the oesophagus. Issue 13 (14th August 2018) - Mine, S.; Watanabe, M.; Kumagai, K.; Okamura, A.; Yamashita, K.; Hayami, M.; Yuda, M.; Imamura, Y.; Ishizuka, N.
Abstract : Background: Treatment of supraclavicular nodes remains controversial among patients with oesophageal squamous cell carcinoma. This study assessed the outcomes of patients who underwent oesophagectomy with or without supraclavicular lymphadenectomy after neoadjuvant treatment. Methods: This was a single‐centre retrospective cohort study. Patients with oesophageal squamous cell carcinoma and clinically negative supraclavicular nodes who underwent oesophagectomy after neoadjuvant treatment between January 2005 and December 2015 were included. Overall and relapse‐free survival were compared between patients who did or did not undergo supraclavicular nodal dissection. Propensity score matching was used to correct for differences in prognostic factors between the groups. Results: Some 223 patients underwent supraclavicular lymphadenectomy. The prevalence of pathologically confirmed supraclavicular metastasis was 10·3 per cent, and these patients had poor 5‐year relapse‐free (7 per cent) and overall (14 per cent) survival. Only two of 55 patients who did not undergo supraclavicular lymphadenectomy had recurrent disease in the supraclavicular region without distant metastasis. There was no statistically significant difference between the groups in relapse‐free survival (hazard ratio (HR) 0·95, 95 per cent c.i. 0·61 to 1·47; P  = 0·821) or overall survival (HR 0·86, 0·52 to 1·40; P  = 0·544). Similarly, no significant difference in relapse‐free or overall survival was observed between the propensity score‐matched groups. Conclusion: For patients with clinically negative supraclavicular lymph nodes, prophylactic supraclavicular lymphadenectomy may be omitted when neoadjuvant treatment is administered. Abstract : Extended dissection not needed